THE PROPOSED MODEL OF THE G*GOLD WAY STRATEGY FOR TEACHERS TO IMPLEMENT THE “KURIKULUM MERDEKA” AT ALL SCHOOL LEVELS - Supriyono, Supriyono (Journal of Innovation Research and Knowledge, 2022)
This paper aims at designing The proposed G*GOLD Way Strategy for teachers to implement the so-called Kurikulum Merdeka At All School Levels in Indonesia. This proposed strategy was the result of Phenomenological and theoretical Synthesis Analysis. The analysis was done with reference to the descriptive qualitative research design. The new Indonesian movement of the Freedom Curriculum has aroused the need for teachers’ assistance in designing a strategy for the so-called Kurikulum Merdeka implementation. Based on the need analysis, theoretical analysis of the curriculum and learning, and the analysis of G*GOLD principles, The modeling strategy was revealed to consist of ways to integrate the so-called 5 (five) ways to star teachers utilizing the principles of Greatness, Gratitude, Obedience, Love, and Discipline with the star mindset and the so-called JACK-B and Positivism Attitudes. Such strategies are parts of the instructional management and therefore considerations of the planning, implementation, and evaluation were included in the model. Further research in the forms of experimental research, case study, or research and development is advised to be done for strengthening the scientific and practical contribution to the Indonesian Curriculum Movement.